The Eye-Size Illusion: Psychophysical Characteristics, Generality, and Relation to Holistic Face Processing. (April 2014) - Xiao, Wen S; Fu, Genyue; Quinn, Paul C; Sun, Yu-Hao; Xiao, Naiqi G; Wang, Qiandong; Chen, Guowei; Pascalis, Olivier; Damon, Fabrice; Lee, Kang
Rakover [(2011). In Y. H. Zhang (Ed.), Advances in face image analysis: Techniques and technologies (pp. 316–333). Hershey, PA: IGI Global] observed a novel eye-size illusion: When increasing the size of a face but keeping the size of its eyes unchanged, the eyes are perceived to be smaller than in the original face. Here, we systematically manipulated the face size and found that the magnitude of this illusion linearly changed as a function of the face frame size (experiment 1). Additionally, the same magnitude of an illusion was observed for the perception of the size of the mouth when we changed the face frame but kept the mouth size constant (experiment 2). Further, when the faces and eyes were presented upside down, the magnitude of the illusion was significantly reduced in both Chinese participants (experiment 3) and Caucasian participants (experiment 4). The results suggest that the perception of eye or mouth size occurs in the relational context of the whole face; and when the face is inverted, thereby disrupting holistic processing, the magnitude of the illusion is reduced. We therefore suggest that holistic processing is involved in producing the illusion.